The raptor Chimango Caracara (Milvago chimango) (Aves: Falconiformes) - A new host for Trichomonas gallinae (protozoa: Trichomonadidae). (December 2019) - Pinheiro Bruni, Mirian; Vargas Zillig Echenique, Joanna; Caetano dos Santos, Carolina; Pegoraro de Macedo, Marcia Raquel; Mota Bandarra, Paulo; Dias Timm, Cláudio; Pereira Schild, Ana Lúcia; Lopes Ruas, Jerônimo; Pereira Soares, Mauro; da Rosa Farias, Nara Amélia
Abstract: This work describes a specimen of Chimango Caracara ( Milvago chimango - Vieillot, 1816), from southern Brazil, as a new natural host for Trichomonas gallinae (Rivolta, 1878). Caseous oral lesions were observed in a young bird, and the parasite was isolated in modified Diamond's media. Morphology of the parasite was evaluated through microscopy and subsequently, sequencing of the internal transcribed spacer 1 (ITS1) of ribosomal DNA was performed to confirm T. gallinae identification. As far as authors are concerned, this is the first report of Milvago chimango as a natural host for T. gallinae . Graphical abstract: Image 1 Highlights: This is the first report of Milvago chimango as a natural host for T. gallinae . The in vitro culture and molecular analysis allowed the confirmation of the diagnosis of trichomonosis. Wild species adapted to urban environments may pose new risks to the wild fauna.